Senataxin homologue Sen1 is required for efficient termination of RNA polymerase III transcription. (11th July 2019) - Rivosecchi, Julieta; Larochelle, Marc; Teste, Camille; Grenier, Frédéric; Malapert, Amélie; Ricci, Emiliano P; Bernard, Pascal; Bachand, François; Vanoosthuyse, Vincent
Abstract: R‐loop disassembly by the human helicase Senataxin contributes to genome integrity and to proper transcription termination at a subset of RNA polymerase II genes. Whether Senataxin also contributes to transcription termination at other classes of genes has remained unclear. Here, we show that Sen1, one of two fission yeast homologues of Senataxin, promotes efficient termination of RNA polymerase III (RNAP3) transcription in vivo . In the absence of Sen1, RNAP3 accumulates downstream of RNAP3‐transcribed genes and produces long exosome‐sensitive 3′‐extended transcripts. Importantly, neither of these defects was affected by the removal of R‐loops. The finding that Sen1 acts as an ancillary factor for RNAP3 transcription termination in vivo challenges the pre‐existing view that RNAP3 terminates transcription autonomously. We propose that Sen1 is a cofactor for transcription termination that has been co‐opted by different RNA polymerases in the course of evolution. Synopsis: Fission yeast expresses two Senataxin helicase homologs, Sen1 and Dbl8. Sen1 is now shown to be required for efficient RNA polymerase III transcription termination of a subset of transcripts, challenging models of RNAP3 terminating transcription autonomously. RNAP3 interacts with Sen1 but not Dbl8 in fission yeast. Sen1 is required for normal RNAP3 transcription. Sen1 prevents the accumulation of exosome‐sensitive read‐through transcripts. Sen1 acts independently of R‐loops at RNAP3‐transcribed genes. Abstract : One of two fission yeast homologs of the helicase Senataxin interacts with RNAP3, preventing its accumulation downstream of transcribed genes and production of exosome‐sensitive read‐through transcripts.